Effect of age at the beginning of the free-range fattening period on growth and carcass and fat quality in Iberian pigs (Archives of Animal Nutrition, 2006)
Abstract This experiment was carried out to study the influence of age at the beginning of the free-range fattening period (traditional pigs, TP, age 12 months vs. young pigs, YP, age 8 months) on the performance of Iberian pigs. During 152 days prior to the fattening period, TP and YP pigs received 1.7 and 2.6 kg feed per day, respectively. During fattening, TP pigs had a higher average daily gain (p < 0.05) than YP pigs. The proportions of PUFA and n-3 fatty acids of the outer and inner layers of subcutaneous backfat were higher in TP than in YP pigs (p < 0.05), while the proportions of C16:0 and SFA in the inner layer of subcutaneous backfat were greater in YP than in TP pigs (p < 0.05). The ratio of n-6/n-3 in subcutaneous backfat was lower in TP than in YP pigs (p < 0.05). The percentage of intramuscular fat in longissimus dorsi muscle was higher in TP than in YP pigs (p < 0.05). The relationship between the percentage of intramuscular fat in longissimus dorsi muscle and average daily gain during the free-range fattening period adjusted to a quadratic function (p < 0.05). The concentration of α- and ?-tocopherol in subcutaneous backfat at slaughter was significantly higher in TP than in YP pigs (p < 0.05). It is concluded that Iberian pigs that have 8 months of age at the beginning of free-range feeding have adequate commercial quality.
From Duplicate 2 (Effect of age at the beginning of the free-range fattening period on growth and carcass and fat quality in Iberian pigs - Daza, Argimiro; López-Bote, Clemente; Rey, Ana; Olivares, Álvaro)